Characterization of the Proteasome Accessory Factor (paf) Operon in Mycobacterium tuberculosis - Festa, Richard A. (American Society for Microbiology, 2007)
In a previous screen for Mycobacterium tuberculosis mutants that are hypersusceptible to reactive nitrogen intermediates (RNI), two genes associated with the M. tuberculosis proteasome were identified. One of these genes, pafA (proteasome accessory factor A), encodes a protein of unknown function. In this work, we determined that pafA is in an operon with two additional genes, pafB and pafC. In order to assess the contribution of these genes to RNI resistance, we isolated mutants with transposon insertions in pafB and pafC. In contrast to the pafA mutant, the pafB and pafC mutants were not severely sensitized to RNI, but pafB and pafC were nonetheless required for full RNI resistance. We also found that PafB and PafC interact with each other and that each is likely required for the stability of the other protein in M. tuberculosis. Finally, we show that the presence of PafA, but not PafB or PafC, regulates the steady-state levels of three proteasome substrates. Taken together, these data demonstrate that PafA, but not PafB or PafC, is critical for maintaining the steady-state levels of known proteasome substrates, whereas all three proteins appear to play a role in RNI resistance.